Regulators of RNA m5C methylation are adipose tissue depot-specific expressed and correlate with clinical variables of obesity in humans - Svensson, Stina Ingrid Alice; Hoffmann, Anne; Hagemann, Tobias; Cayir, Akin; Saeed, Sadia; Ghosh, Adhideb; Wolfrum, Christian; Blüher, Matthias; Böttcher, Yvonne (Frontiers in Endocrinology, 2025)
BackgroundObesity is a global health burden and recent evidence indicates that epitranscriptomic regulation is potentially involved in its etiology. The epitranscriptomic mark 5-methylcytosine (m5C) is implicated in cancer and recent data linked the gene expression of m5C writers, erasers and readers to diabetes, a well-known co-morbidity of obesity. Here, we tested whether gene expression of m5C regulators in paired samples of human visceral and subcutaneous adipose tissue is (i) adipose tissue depot-specific and (ii) correlates with important clinical variables of obesity.MethodsIntra-individually paired adipose tissue samples from human subcutaneous adipose tissue (SAT) and omental visceral adipose tissue (OVAT) were utilized from three different cohorts from the Leipzig Obesity Biobank including a large cross-sectional cohort, a two-step bariatric surgery cohort and a cohort of metabolically healthy vs unhealthy individuals (LOBB, total N=962). Data analysis on intra-individual samples was performed by using the paired Wilcoxon signed-rank test, while in comparisons on independent groups the unpaired Wilcoxon rank-sum test was employed. Bonferroni correction method was used to adjust multiple testing of p-values and Spearman’s rank correlation was used to assess associations.ResultsWe observed that multiple m5C regulators were differentially expressed between human subcutaneous and visceral adipose tissue depots. Interestingly, we found that for several regulators the effects were less pronounced after weight loss, whilst stronger in individuals with insulin resistance compared to their healthy counterparts. A strong correlation of m5C regulator expression with macrophages was observed in OVAT compared to its SAT counterpart. Correlations between m5C regulators with important clinical variables related to obesity were observed in all three cohorts.ConclusionOur findings provide evidence for adipose tissue depot-specific gene expression of m5C regulators that correlate with clinical variables of obesity.